Stability and Blowout Behavior of Jet Flames in Oblique Air Flows - Jonathan N. Gomes; James D. Kribs; Kevin M. Lyons (Journal of Combustion)
The stability limits of a jet flame can play an important role in the design of burners and combustors. This study details an experiment conducted to determine the liftoff and blowout velocities of oblique-angle methane jet flames under various air coflow velocities. A nozzle was mounted on a telescoping boom to allow for an adjustable burner angle relative to a vertical coflow. Twenty-four flow configurations were established using six burner nozzle angles and four coflow velocities. Measurements of the fuel supply velocity during liftoff and blowout were compared against two parameters: nozzle angle and coflow velocity. The resulting correlations indicated that flames at more oblique angles have a greater upper stability limit and were more resistant to changes in coflow velocity. This behavior occurs due to a lower effective coflow velocity at angles more oblique to the coflow direction. Additionally, stability limits were determined for flames in crossflow and mild counterflow configurations, and a relationship between the liftoff and blowout velocities was observed. For flames in crossflow and counterflow, the stability limits are higher. Further studies may include more angle and coflow combinations, as well as the effect of diluents or different fuel types.